Upaya Meningkatkan Hasil Belajar IPS Ekonomi dengan Menggunakan Model Pembelajaran Kooperatif Tipe Snowball Throwing pada Kelas VIII MTS Hidayatul Insan Palangka Raya - Raudah Raudah; Isna Mariani (Neraca: Jurnal Pendidikan Ekonomi, 2018)
This study aims to determine learning activities and learning outcomes. This type of research is Class Action Research (CAR). The subjects of this study were class VIII students of Usman bin Affan, MTs Hidayatul, Palangka Raya Individuals totalling 17 students. This data collection technique is observation and testing. Data analysis techniques are based on the results of the cycle during the learning process. The results of the study concluded that: (1) learning activities of students in Economics Social Studies learning by applying the cooperative learning model Snowball Throwing type in class VIII Usman bin Affan MTs Hidayatul Insanity Palangka Raya was more active, (2) there was an increase in Social Economics learning outcomes after applying the model cooperative learning Type Snowball Throwing on class VIII students of Usman bin Affan MTs Hidayatul Insan Palangka Raya.